0 Deepak Bora Asked: July 14, 20202020-07-14T23:39:50+05:30 2020-07-14T23:39:50+05:30In: CBSE, ICSE Prove that : cosec^6θ -cot^6θ = 3 cot^2θcosec^2θ +1 0 Prove this standard identity using algebraic identity (a+b)³=a³+b³+3ab(a+b) : cosec^6θ -cot^6θ = 3 cot²θcosec²θ +1. trigonometric provingtrigonometrytrigonometry formulas Share Facebook Related Questions If tanθ=4/3, show that (sinθ+cosθ)=7/5 If cosec θ= 2 show that (cot θ + sin θ / 1 + cos θ) = 2 If 15cotA = 8, find the values of sin A and secA. If sin θ= √3/2, find the value of all T-ratios of θ A T.V. Tower stands vertically on a bank of a river. From a point on the other bank ... 1 Answer Voted Oldest Recent Deepak Bora 2020-07-15T12:15:03+05:30Added an answer on July 15, 2020 at 12:15 pm This answer was edited. IDENTITY -( 1 + cot^2A ) = cosec^2A 0 Reply Share Share Share on Facebook Share on Twitter Share on LinkedIn Share on WhatsApp Leave an answerLeave an answerCancel reply Featured image Select file Browse Add a Video to describe the problem better. Video type Youtube Vimeo Dailymotion Facebook Choose from here the video type. Video ID Put Video ID here: https://www.youtube.com/watch?v=sdUUx5FdySs Ex: "sdUUx5FdySs". Click on image to update the captcha. Save my name, email, and website in this browser for the next time I comment.